Bandgap Energy of TiO₂/M-Chlorophyll Material (M=Cu²⁺, Fe³⁺) - Muhammad Yusprianto; Titin Anita Zaharah; Imelda Hotmarisi Silalahi (Jurnal Kimia Sains dan Aplikasi, 2021)
The bandgap energy (Egap) of TiO2 material modified with metal-chlorophyll complex compounds (M = Cu2+, Fe3+) was observed. Chlorophyll (Chl) was isolated from cassava leaves, and its UV-Vis spectra showed absorption peaks in the Soret band region (410 nm) and in the Q band region (665 nm), which is the typical peak of chlorophyll. Copper(II)-chlorophyll complex was prepared from the reaction between chlorophyll and CuSO4.5H2O, while the iron(III)-chlorophyll was synthesized from chlorophyll and FeCl3.6H2O in methanol solvent under reflux at 65°C. The presence of copperand iron metals in the chlorophyll metal complexes was identified using Atomic Absorption Spectroscopy in methanol solution. The absorption of copper measured in Cu2+-Chl was 0.0488 (0.4805 mg/L), while the iron atom in Fe3+-Chl was 0.0050 (0.0195 mg/L). The UV-vis spectra demonstrate the hypsochromic shift of the Soret band to 405 nm (Cu2+-Chl) and 402 nm (Fe3+-Chl). The Infrared spectra of chlorophyll after being complexed with copper(II) shows the increase of vibrational absorption wavenumber of the C=N group from 1225.06 cm-1 to 1241.94 cm-1 indicates the coordination of the metal ion on the N atom in the pyrrole ring. The shift in the absorption band on the Fe3+-Chl spectrum was seen for the C=O ester group from 1720.49 cm-1 to 1721.10 cm-1 indicating the metal ion bonding in the C=O group of esters. The DR-UVis analysis of TiO2/metal-chlorophyll shows a bathochromic shift towards the visible light region. By using the Tauc plot method, it was observed that the Egap of TiO2 reduces from 3.08 eV to 2.89 eV and 2.93 eV in the compound of TiO2/Cu2+-Chl and TiO2/Fe3+-Chl, respectively.